Teacher Professional Development in Higher Education: The Impact of Pedagogical Training Perceived by Teachers - Sandra Fernandes; Alexandra M. Araújo; Isabel Miguel; Marta Abelha (MDPI AG, 2023)
This paper aims to analyze the impact of a pedagogical training program aimed to promote teacher professional development in a higher education institution in Portugal. Based on a mixed-methods approach, the study evaluates the satisfaction of 36 higher education teachers with the pedagogical training program offered and discusses its impact on teachers' perceptions of teaching practices, conceptions, and professional development. The results from the questionnaires applied to participants, including multiple choice questions and open-ended answers, indicate high satisfaction with the implemented training program. Based on this case study, the authors discuss the implications of findings for teacher professional development and identify key characteristics for the design of successful pedagogical training programs in higher education.